Sundanese Language Maintenance in Cianjur City (Ethnographic Research) - Kurniawati, Wati; Emzir,; Akhadiah, Sabarti (International Journal of Scientific Research and Management (IJSRM), 2020)
This research aims to analyse the process of the Sundanese language maintenance in the city of Cianjur, West Java Province by using ethnographic methods. The focus of observations based on the classification of five subfocuses, which is the choice of language and the domain of use, the language attitude of the speakers, factors that threaten the existence of Sundanese language, the preservation of Sundanese language, and the vitality of Sundanese the results showed; (1) The domain of the use, the speech between parents and children in Sundanese, on Wednesday using Sundanese language among employees, the process of marriage in Sundanese language except when the Indonesian government, and the process of trading also using Sundanese language, (2) Language attitudes, Sundanese speakers are positive towards the language, and the government protects the Sundanese language based on local laws and regulations, (3) Threatening factors, internal factors include weakening transmission of regional cultural values, regional languages into marginal language (e.g., in the educational curriculum as local content taught only two hours of lessons in a week), lack of awareness of the young generation in preserving the regional language while external factors are modernization and globalization, the existence of foreign language in Indonesian, and cultural domination, (4) Preservation efforts, foster positive attitude, loyalty, pride, awareness of the language norms of Sundanese, the use of everyday Sundanese language, the presence of inter-generational transmissions, the use of Sundanese in public spaces, a deeper loading of the curriculum, the absorption of vocabulary from various languages, cultural festivals and literacy, and (5) The vitality of the Sundanese language at age groups of 0-14 years tends to the younger generation still uses the Sundanese language when it says to children, but the children sometimes answer the Indonesian language, the vitality of the Sundanese language in the language that serves as a bilingual equality or Multilingual decline.